Importance of intracellular pH in determining the uptake and efficacy of the weakly basic chemotherapeutic drug, doxorubicin. - Pawel Swietach; Alzbeta Hulikova; Shalini Patiar; Richard D Vaughan-Jones; Adrian L Harris (PLoS ONE)
Low extracellular pH (pH(e)), that is characteristic of many tumours, tends to reduce the uptake of weakly basic drugs, such as doxorubicin, thereby conferring a degree of physiological resistance to chemotherapy. It has been assumed, from pH-partition theory, that the effect of intracellular pH (pH(i)) is symmetrically opposite, although this has not been tested experimentally. Doxorubicin uptake into colon HCT116 cells was measured using the drug's intrinsic fluorescence under conditions that alter pH(i) and pH(e) or pH(i) alone. Acutely, doxorubicin influx across the cell-membrane correlates with the trans-membrane pH-gradient (facilitated at alkaline pH(e) and acidic pH(i)). However, the protonated molecule is not completely membrane-impermeant and, therefore, overall drug uptake is less pH(e)-sensitive than expected from pH-partitioning. Once inside cells, doxorubicin associates with slowly-releasing nuclear binding sites. The occupancy of these sites increases with pH(i), such that steady-state drug uptake can be greater with alkaline cytoplasm, in contradiction to pH-partition theory. Measurements of cell proliferation demonstrate that doxorubicin efficacy is enhanced at alkaline pH(i) and that pH-partition theory is inadequate to account for this. The limitations in the predictive power of pH-partition theory arise because it only accounts for the pH(i)/pH(e)-sensitivity of drug entry into cells but not the drug's subsequent interactions that, independently, show pH(i)-dependence. In summary, doxorubicin uptake into cells is favoured by high pH(e) and high pH(i). This modified formalism should be taken into account when designing manoeuvres aimed at increasing doxorubicin efficacy.